Assessment of effectiveness of Cinemeducation as a tool to impart communication skills among the MBBS 1st Professional students - Bartwal, Janki; Shukla, Mukesh (Indian Journal of Community Health, 2022)
Background: Improvements in healthcare providers’ communication skills have been linked to more effective healthcare delivery, improved patient compliance, better patient and provider satisfaction, and fewer lawsuits. Cinemeducation is a relatively new method of medical education where movies or movie clips are used to stimulate discussions and reflections, which is a part of an active learning process. Hence, the present study was undertaken. Methods: We conducted an educational research, mixed method study among the MBBS 1st Professional students. A pre & post test to assess the knowledge and attitude of the students about the importance of communication skills in doctor-patient relationship. Students wrote the reflection and feedback after watching the movie clip. Quantitative analysis was done using paired t test by SPSS v. 20. Qualitative data analysis was done by two investigators independently. Results: The pre & post test for knowledge was statistically significant while communication skill attitude scale score for both positive & negative was not significant. Conclusion: The student’s knowledge improved significantly after the sessions on communication skills, while negligible change in attitude was observed. Reflective writing by the students shows that cinemeducation can be used as one of the tool for teaching communication skills to the medical students.